Matriz gesto-vocal da linguagem de uma criança em interação com outros interlocutores durante o reconto de história. - Santos, Ana Célia Guimarães dos (2025)
In any field of language acquisition, the number of research on gestures and other modalities of language use has intensified from a multimodal linguistic perspective, which has contributed to raising the scientific status of the topic. In this context, this research is based on the multimodal perspective of language, in which gesture and vocal production are part of the same system of meaning, as argued by Kendon (1982; 2016), McNeill (1992), Fonte et al . (2014), Cavalcante et al. (2015), among others.In this sense, studies have demonstrated how oral narratives can be considered multimodal narratives, such as the retelling of stories done by children, a situation that evokes the use of multimodal resources in the narration process, as stated by Almeida (2018). Therefore, the objective of this research was to investigate the gesture-vocal matrix of language in a child based on the interaction with the mother and the researcher during story telling. Methodologically, a longitudinal case study and a qualitative approach were carried out. At the beginning of the research, the child's age was 2 years, 6 months and 15 days and we observed him in five moments over a period of 38 days. The recordings were made in the home environment during the telling and retelling of the stories. The collected material was transcribed using the ELAN software. As a contribution to the analysis, the gestural categories addressed by Kendon (1982; 2016) were considered: gesticulation, filling gestures, pantomime and emblematic gestures; the gestural dimensions formulated by McNeill (1992): iconic, metaphorical, deictic and rhythmic gestures; the prosodic-vocal categories worked by Almeida (2018): babbling, jargon, holophrases and blocks of utterances; and the notion of protonarratives presented by Perroni (1983). On the child's vocal level, we observed the constant use of holophrases and blocks of utterances, confirming that prosodic-vocal functioning is not static, as children at the same age may use more than one of these categories. At the gestural level, we found a greater recurrence of deictic gestures associated with the interaction game, sometimes associated with holophrases, fulfilling the role of indicating characters or elements of the narrative plot, and pantomimes, in several scenes produced together with voice modulations ( vocal pantomimes), representing the actions of characters. We understand that during the sessions there was an evolution in the use of multimodal resources by the child, who began to demonstrate a more conscious use of productions, better balancing the use between gestures and vocal productions in the last session. In many moments, the object (book) was the interactive focus of joint attention. Therefore, we believe that the results of this study contribute significantly to the understanding of the functioning of the gesture-vocal matrix, reiterating its uses and the interactive dynamics with children in the context of the narrative process. These findings also provide support for future research in the field of education, allowing teachers to promote experiences based on this perspective, facilitating the development of children's narratives. In this way, we seek to broaden the vision of educators and society in general by highlighting that the child, even before fully mastering oral production, is already a communicative agent. It is also expressed through gestures, looks and facial expressions, that is, through multimodal aspects that constitute language.